Impression management in corporate corruption settlements: The storied self of the prosecutorial authority - Capus, Nadja; Bozinova, Melody (My University, 2023)
Transnational corporate bribery cases are increasingly resolved through non-trial resolutions called settlements. These settlements lead to a considerable shift of the prosecutorial authority’s role. Drawing on Goffman’s impression management framework (1959), this article conceptualises settlement procedures as ‘backstage criminal justice’ that aims to shield criminal justice practice from public view and showcase a team-crafted narrative. Our narrative analysis of a publicly available settlement in England and Wales investigates the prosecutorial authority’s impression management strategies within settlement storytelling. The analysis reveals three distinct and sometimes conflicting narratives of the prosecutorial role in settling criminal justice. These conflicting narratives reflect the ambiguities inherent in enforcing national criminal laws transnationally against economically relevant companies.
Keywords: impression management; settlement storytelling; prosecutor; corporate bribery; deferred prosecution agreements; narrative criminology